STUDI SOSIO LEGAL DALAM PEMANFAATAN ENERGI TERBARUKAN DI PERAIRAN INDONESIA - Purba, Marlina (Jurnal Hukum & Pembangunan, 2021)
Socio-legal studies are the kind of study that presents the point of view to see the law which focuses on the contact more than the texts. By legal socio approach, the problem which will be learned is notonly study to the norms studied or the law doctrine but see the contact detail of the norms and the enactment. How the law work in the public which will be learned by legal socio study. The legal socio study is done by refer to the research result Cotterrell R about the theory and value. Cotterrell enters the value to explain the action of the social and the law, while the theory plays the role to dig the values which exist in the attitude to the law, the attitude to the practice of interpretation, and thelaw application also to the perception on two different interests. The theory and any value which iscan bethe material of legal socio study in the utilization of renewable energy which is come from the sea is become to be the result of this study.